Bone health status and lipid profile among post-menopausal Malay women in Cheras, Kuala Lumpur - Haron, Hasnah; Ismail, Amin; Shahar, Suzana (Nutrition Society of Malaysia, 2012)
Introduction: A cross-sectional study was conducted to determine bone health status and nutrient intakes among post-menopausal women residing in low cost houses in Cheras, Kuala Lumpur. Methods: A total of 125 subjects aged 60 ± 4 years who had attained menopause at age 50 ± 5 years participated in this study. Subjects’ weight and height were measured and calculated for body mass index (BMI). They were also assessed for bone health status using the Quantitative Ultrasound (QUS). Nutrient intake was assessed using a dietary history Questionnaire. Fasting serum lipid and blood pressure measurements were also taken. Results: The majority of the subjects were overweight and obese (80%) based on BMI status. Calcaneal measurements using the QUS indicated that while 57% or the subjects had normal bone mineral density, 37% were osteopenic and 6% osteoporotic. Calcium intake of the subjects was 505 ± 263mg /day, which is only 50% of the Malaysian Recommended Nutrient Intake for calcium (1000 mg/d). About 74% of the subjects were hypercholesterolemic and 58% were hypertriglyceridemic. Two-thirds reported that they were taking medication for hypertension, diabetes mellitus and heart disease. Conclusion: The results showed low health and nutritional status among post-menopausal women living in low-cost flats in Kuala Lumpur. They have low bone mass which may be due to their predominantly non-milk based diets which places them at high risk of hip fractures. Apart from milk, other food sources of calcium, including soya bean products such as ‘tempeh’ and healthy ways of cooking should be recommended to older people.